2017
DOI: 10.1177/1010428317707437
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidumtargeting lung cancer signaling: A review

Abstract: Lung cancer causes huge mortality to population, and pharmaceutical companies require new drugs as an alternative either synthetic or natural targeting lung cancer. The conventional therapies cause side effects, and therefore, natural products are used as a therapeutic candidate in lung cancer. Chemical diversity among natural products highlights the impact of evolution and survival of fittest. One such neglected natural product is Ganoderma lucidum used for promoting health and longevity for a longer time. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 61 publications
0
13
0
4
Order By: Relevance
“…Ganoderma contains many bioactive natural components, including triterpenes, polysaccharides, proteins and steroids. Ganoderma triterpenoids and steroids were reported to be potential chemopreventive and therapeutic agents for cancer treatment ( 13 , 14 ). 9(11)-DHEP is a natural product present in G. lucidum , which has been shown to regulate various biological process.…”
Section: Discussionmentioning
confidence: 99%
“…Ganoderma contains many bioactive natural components, including triterpenes, polysaccharides, proteins and steroids. Ganoderma triterpenoids and steroids were reported to be potential chemopreventive and therapeutic agents for cancer treatment ( 13 , 14 ). 9(11)-DHEP is a natural product present in G. lucidum , which has been shown to regulate various biological process.…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer activities of GLP have remained a focus of interest for cancer prevention. Numerous studies have demonstrated that GLP is able to inhibit carcinogenesis in various types of cancer, including ovarian ( 41 ), lung ( 42 , 43 ), breast ( 44 ), liver cancer ( 45 ), leukemia ( 46 ), colon cancer ( 22 ) and PCa ( 47 ). Amongst these cancer types, the anticancer effects of G. lucidum on PCa have been the most intensely investigated; this is due to earlier reports on PC-SPES and its anticancer activity in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, GLP has been found to have antioxidant [9,10], immunoregulation [11,12], anti-inflammatory [13], and anticancer [14,15] properties. Recently, some evidence has found that the bioactive components of ganoderma lucidum, including polysaccharide, can regulate cell cycle, apoptosis, and autophagy in lung cancer [16]. Lieu et al [17] discovered that GLP could suppress the growth and differentiation of leukemic U937 cells.…”
Section: Introductionmentioning
confidence: 99%